Laparosopic cholecystectomy. Initial experience of two university services - Cazabán, Luis A; Genta, Fernando; Hermida, Mario (Cirugía del Uruguay, 1998)
The aim of this paper was to evaluate the results of laparoscopic cho/ecystectomy at the Hospital de Clínicas. The first 147 coordination laparoscopic cholecystectomies performed at the "A" and "B" Surgical Clinics mainly by trainee surgeons between June 1992 and September 1996 are analysed. Clinical, biological and imagenological features were used and predictive features far choledochal lithiasis. French technique was employed in 70% of the cases and american technique in 30%. There were 29 performing surgeons. Maximum number of procedures per surgeon was 24 and mínimum one. In 43% of the cases selective cholangiography was performed, Conversion rate was 4,8%. Average operating time was 117 minutes. There were postoperative complications in 4, 7% of the cases, inc!uding two lesions of the main biliar via. Operative mortality was ni/ and average discharge from hospital was three days and eight hours